Variation in the Cost of Care for Different Types of Joint Arthroplasty. (4th March 2020) - Carducci, Michael P.; Gasbarro, Gregory; Menendez, Mariano E.; Mahendraraj, Kuhan A.; Mattingly, David A.; Talmo, Carl; Jawa, Andrew
Abstract : Background: Lower-extremity arthroplasty constitutes the largest burden on health-care spending of any Medicare diagnosis group. Demand for upper extremity arthroplasty also continues to rise. It is necessary to better understand costs as health care shifts toward a bundled-payment accounting approach. We aimed (1) to identify whether variation exists in total cost for different types of joint arthroplasty, and, if so, (2) to determine which cost parameters drive this variation. Methods: The cost of the episode of inpatient care for 22, 215 total joint arthroplasties was calculated by implementing time-driven activity-based costing (TDABC) at a single orthopaedic specialty hospital from 2015 to 2018. Implant price, supply costs, personnel costs, and length of stay for total knee, total hip, anatomic total shoulder, reverse total shoulder, total elbow, and total ankle arthroplasty were analyzed. Individual cost parameters were compared with total cost and volume. Results: Higher implant cost appeared to correlate with higher total costs and represented 53.8% of the total cost for an inpatient care cycle. Total knee arthroplasty was the least-expensive and highest-volume procedure, whereas total elbow arthroplasty had the lowest volume and highest cost (1.65 times more than that of total knee arthroplasty). Length of stay was correlated with increased personnel cost but did not have a significant effect on total cost. Conclusions: Total inpatient cost at our orthopaedic specialty hospital varied by up to a factor of 1.65 between different fields of arthroplasty. The highest-volume procedures—total knee and hip arthroplasty—were the least expensive, driven predominantly by lower implant purchase prices. Clinical Relevance: We are not aware of any previous studies that have accurately compared cost structures across upper and lower-extremity arthroplasty with a uniform methodology. The present study, because of its uniform accounting process, provides reliable data that will allow clinicians to better understand cost relationships between different procedures.